The Role of Profitability in Weakening the Effect of Environmental Performance on Environmental Disclosure - Cahyaningsih Cahyaningsih; Denna Taris Citra Rahadiansyah (Postgraduate Program Merdeka University, 2023)
This research aims to investigate the effect of environmental performance, institutional ownership, and profitability on environmental disclosure, with profitability as a moderating variable. Based on the sample selection criteria, this study analyzed 18 companies from the energy, raw goods, and primary consumer goods sectors listed on the Indonesia Stock Exchange for the 2019-2021 period. The data analysis technique in this study used panel data regression and moderated regression analysis. The results show that environmental performance and institutional ownership positively affect environmental disclosure in contrast to profitability which does not affect environmental disclosure. This research finds that profitability weakens the effect of environmental performance on environmental disclosure. Other results show that profitability cannot moderate the effect of institutional ownership on environmental disclosure. This finding indicates that companies use excess resources to increase investment, not to improve environmental performance and disclosure.DOI: https://doi.org/10.26905/afr.v6i3.10593